The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10018-010-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Discounting in the context of climate change economics: the policy implications of uncertainty and global asymmetries

Abstract: Climate change, Discounting, Risk, Uncertainty, Asymmetries,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Building on recent advances that demonstrated the reduction effect of engagement in EFT on the tendency to discount the future [10][11][12][13][14][15] and the association between the discounting tendency and climate change engagement [5][6][7][8], we contend that engagement in EFT to envisage life events involving mitigation action may induce a lower discounting tendency and enhance the tendency to engage in pro-environmental action. We found that engaging in EFT associated with mitigation events promoted the inclination to act pro-environmentally, as reflected by a greater tendency to use air conditioning in an energy-saving manner (Experiment 1), a higher likelihood of choosing a diet with lower environmental impact (Experiment 2), and a higher inclination to participate in beach cleaning (Experiment 2).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Building on recent advances that demonstrated the reduction effect of engagement in EFT on the tendency to discount the future [10][11][12][13][14][15] and the association between the discounting tendency and climate change engagement [5][6][7][8], we contend that engagement in EFT to envisage life events involving mitigation action may induce a lower discounting tendency and enhance the tendency to engage in pro-environmental action. We found that engaging in EFT associated with mitigation events promoted the inclination to act pro-environmentally, as reflected by a greater tendency to use air conditioning in an energy-saving manner (Experiment 1), a higher likelihood of choosing a diet with lower environmental impact (Experiment 2), and a higher inclination to participate in beach cleaning (Experiment 2).…”
Section: Discussionmentioning
confidence: 83%
“…Communications of the future impacts of climate change have been framed as distant threats [2,8]. At the individual level, the discounting of a future risk such as climate change represents a pervasive tendency in which daily, immediate concerns take precedence over remote threats [5,28]. A viable explanation for less engagement of the general public with climate change is that the negative impacts of climate change tend to be perceived as a set of distant, uncertain events [2,6,8,29].…”
Section: The Discounting Tendency and Pro-environmental Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Choosing the value of the discount rate, i , for economic costs and especially for greenhouse gas emissions is not without difficulties, and is significant as PVA is highly sensitive to the value of the discount rate. Many studies have addressed the choice of discount rate [ Simpson , ; Wu et al ., ; Azar and Sterner , ; Conceição et al ., ; Weitzman , ; Rambaud and Torrecillas , ; Guo et al ., ; Wu et al ., ; Cai et al ., ], and a discussion of the issues surrounding this is beyond the scope of the current paper.…”
Section: Methodsmentioning
confidence: 99%